2014
DOI: 10.1377/hlthaff.2014.0307
|View full text |Cite
|
Sign up to set email alerts
|

For-Profit Medicare Home Health Agencies’ Costs Appear Higher And Quality Appears Lower Compared To Nonprofit Agencies

Abstract: For-profit, or proprietary, home health agencies were banned from Medicare until 1980 but now account for a majority of the agencies that provide such services. Medicare home health costs have grown rapidly since the implementation of a risk-based prospective payment system in 2000. We analyzed recent national cost and case-mix-adjusted quality outcomes to assess the performance of for-profit and nonprofit home health agencies. For-profit agencies scored slightly but significantly worse on overall quality indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 17 publications
2
58
0
Order By: Relevance
“…However, given the more favorable case mix of patients, the lower rates of pain-free status at discharge and of pain improvement found at for-profit agencies strongly suggest a lower quality of pain management at these agencies. This is consistent with the lower or comparable quality of home health care associated with for-profit status found in a previous study 41 and different patterns of service provision by profit status of hospice agencies. 42 …”
Section: Discussionsupporting
confidence: 92%
“…However, given the more favorable case mix of patients, the lower rates of pain-free status at discharge and of pain improvement found at for-profit agencies strongly suggest a lower quality of pain management at these agencies. This is consistent with the lower or comparable quality of home health care associated with for-profit status found in a previous study 41 and different patterns of service provision by profit status of hospice agencies. 42 …”
Section: Discussionsupporting
confidence: 92%
“…This study suggests that specific agency‐level characteristics are associated with performance, including Medicare certification and offering full as opposed to partial services. The finding that proprietary ownership of agencies is associated with a low‐performing score extends prior studies and provides a more‐contemporary assessment at the national level. For example, the 2003–07 home health care data were used to assess changes in agency performance after the initiation of Home Health Compare, and it was found that nonprofit agencies showed greater improvement on some quality measures than their counterparts .…”
Section: Discussionsupporting
confidence: 77%
“…Better performance may lead to better care. The association between nursing home and home health performance in quality of care and outcomes has been studied . For example, one study found that individuals receiving care in higher‐quality skilled nursing facilities had lower readmission rates (18%) than those in lower‐quality skilled nursing facilities (22%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' length of enrollment in home health care was longer under the fee‐for‐service payment system if they were served by a for‐profit agency (Grabowski et al , ; Han et al , ). For‐profit agencies incurred higher expenditures, but provided worse quality of care under the PPS (Cabin et al , ).…”
Section: Introductionmentioning
confidence: 99%